Laser-Patterning Engineering for Perovskite Solar Modules with 95% Aperture Ratio - Palma, Alessandro Lorenzo; Matteocci, Fabio; Agresti, Antonio; Pescetelli, Sara; Calabro, Emanuele; Vesce, Luigi; Christiansen, Silke; Schmidt, Michael; Di Carlo, Aldo (IEEE Journal of Photovoltaics, 2017)
Small area hybrid organometal halide perovskite based solar cells reached performances comparable to the multicrystalline silicon wafer cells. However, industrial applications require the scaling-up of devices to module-size. Here, we report the first fully laser-processed large area (14.5 cm2) perovskite solar module with an aperture ratio of 95% and a power conversion efficiency of 9.3%. To obtain this result, we carried out thorough analyses and optimization of three laser processing steps required to realize the serial interconnection of various cells. By analyzing the statistics of the fabricated modules, we show that the error committed over the projected interconnection dimensions is sufficiently low to permit even higher aperture ratios without additional efforts.
Created from Fastlane, Scopus look-up
Keywords: Industrial applications; laser processing; monolithic interconnections; perovskites solar cells; solar modules